Participatory budgeting and civic tech : the revival of citizen engagement - Gilman, Hollie Russon (Georgetown University Press, 2016)
Participatory budgeting is one of the most promising innovations in twenty-first century democracy. It was pioneered abroad but made its first appearance in the United States in 2009 in Chicago local government. Participatory budgeting empowers citizens to identify community needs, work with elected officials to craft budget proposals, and vote on where and how to spend public funds. It is effective at engaging citizens to be meaningful participants in democracy. Unlike other forms of civic engagement, participatory budgeting involves spending real public money on the priorities that the community identifies. Participatory budgeting is catching on in cities across the United States such as Chicago, New York, Boston, Detroit, St. Louis, and San Francisco. Hollie Russon Gilman has written a brief and accessible introduction to participatory budgeting in the United States.